A survey on antiemetics prescribed for children in some selected districts of Sri Lanka - Ranganathan, Shilani Sri; Mayurathan, K.; Fernandopulle, Rohini (My University, 2010)
Objective: To describe the prescription patterns of antiemetics in children in some selected districts of Sri Lanka and describe standard drug utilization variables, potential drug interactions, extent and types of irrational prescribing and rate of off-label use of anti-emetics. Design, setting and methods: Analysis of paediatric prescriptions containing at least one antiemetic dispensed in eight community pharmacies (4 State, 4 Private) located in four different Provinces of Sri Lanka was performed over a period of four weeks by using a structured pre-tested checklist. Standard drug utilization variables including extent and types of irrational prescription were studied. . Results: One hundred and eighty five prescriptions met the criteria; Domperidone was most frequently (89%) prescribed followed by promethazine (10.5%) and metoclopramide (0.5%). Mean age was 4.48 years. Oral liquid dosage-form was prescribed in 54% followed by tablets (32.5%) and suppositories (11%); in 12% the dosage-form was unsuitable for age. Mean dose was 6 mg; 29.5% of the prescriptions carried irrational doses; 30% of prescriptions were off-label. Potential drug interactions with comedications were possible in 17.6% of instances. Majority of these deficiencies in prescription were observed in children younger than six years. Conclusions: Domperidone was the most frequently dispensed anti-emetic for children in the selected districts. Irrational use of domperidone is more prevalent in young (< 6 years) compared to older children.